The literary science of the 'Kafkaesque' - Troscianko, E (2009)
This study provides a precise definition of the term 'Kafkaesque' by enriching literary criticism with scientific theory and practice, including an experiment on readers' responses to Kafka. Dictionary definitions justify taking the term back to its textual origins in Kafka's works, and the works can fruitfully be analysed by investigating how readers engage with them through cognitive processes of imagination. Modern scientific developments posit that vision, imagination, and consciousness should be conceived of not in terms of static pictorialism – reducible to the notion of 'pictures in the head' – but in terms of enaction, i.e. as an ongoing interaction with the external world around us. Most traditional nineteenth-century Realist texts are based on pictorialist assumptions, while Kafka's texts evoke perception non-pictorially and are therefore more cognitively realistic. In his personal writings, Kafka wrestles with problems entailed by pictorialist conceptions of vision, imagination, and the function of language, and comes to enactivist solutions: evocation of perception that does not result in painting static tableaux with words. In his fictional works, Kafka correspondingly evolves a cognitively realistic way of writing to evoke fictional worlds that directly engage the cognitive processes of their readers; Der Proceß is a prime example of the 'Kafkaesque' text and reading experience, defined by being compelling yet simultaneously unsettling. Modulations in narrative perspective and evocation of emotion as enactive also contribute to the experience of the 'Kafkaesque' as compelling; yet Kafka's texts simultaneously unsettle by preventing straightforward emotional identification with the protagonists, and destabilising deep-rooted concepts of selfhood as singular and unified. The theoretical discussion of the 'Kafkaesque' experience as compelling yet unsettling is complemented and refined by an experiment testing readers' responses to a short story by Kafka. The term 'Kafkaesque realism' denotes Kafka's compelling yet unsettling non-pictorial evocation of perception of the fictional world. Kafkaesque realism falls into the broader category of 'cognitive realism', which provides a framework for analysing fictional texts more generally.